2014
DOI: 10.1111/plb.12234
|View full text |Cite|
|
Sign up to set email alerts
|

Plasmodesmata‐located protein overexpression negatively impacts the manifestation of systemic acquired resistance and the long‐distance movement of Defective in Induced Resistance1 in Arabidopsis

Abstract: Systemic acquired resistance (SAR) is a plant defence response that provides immunity to distant uninfected leaves after an initial localised infection. The lipid transfer protein (LTP) Defective in Induced Resistance1 (DIR1) is an essential component of SAR that moves from induced to distant leaves following a SAR-inducing local infection. To understand how DIR1 is transported to distant leaves during SAR, we analysed DIR1 movement in transgenic Arabidopsis lines with reduced cell-to-cell movement caused by t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
37
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 48 publications
(40 citation statements)
references
References 41 publications
3
37
0
Order By: Relevance
“…Consistent with previous reports, total protein levels were higher in phloem exudates collected from SARinduced compared with mock-inoculated leaves (Champigny et al, 2013;Carella et al, 2015), which may suggest that the induction of SAR leads to the mass translocation of a number of proteins through the phloem. If this is indeed true, then significant modifications to companion cell plasmodesmatal pore size are likely required to facilitate increased protein loading into the phloem.…”
Section: The Sar-induced Phloem Proteomesupporting
confidence: 91%
See 3 more Smart Citations
“…Consistent with previous reports, total protein levels were higher in phloem exudates collected from SARinduced compared with mock-inoculated leaves (Champigny et al, 2013;Carella et al, 2015), which may suggest that the induction of SAR leads to the mass translocation of a number of proteins through the phloem. If this is indeed true, then significant modifications to companion cell plasmodesmatal pore size are likely required to facilitate increased protein loading into the phloem.…”
Section: The Sar-induced Phloem Proteomesupporting
confidence: 91%
“…To obtain protein levels suitable for LC-MS/MS, exudates from more than 90 plants per treatment were collected and concentrated using centrifugal concentrators (3-kD cutoff) followed by lyophilization. Similar to previous reports (Champigny et al, 2013;Carella et al, 2015), phloem exudates collected from SAR-induced leaves contained higher total protein levels than exudates collected from mock-induced leaves (Supplemental Fig S1B). Concentrated phloem exudates from two independent experimental replicates were subjected to quantitative LC-MS/MS (Supplemental Data S1).…”
Section: Quantitative Proteomics Of Phloem Exudates During Sarsupporting
confidence: 89%
See 2 more Smart Citations
“…The signal transduction process and its timing are essential components of SAR induction that moves from induced to distant leaves. Recent studies indicated that the movement of SAR signal(s) is connected to plasmodesmata [10].…”
Section: Introductionmentioning
confidence: 99%